Proximal radial neck fracture with complete 180-degree rotation of radial head: a case report - Imran Ali Shah; Mahenau Hasan Afridi; Muhammad Aarish Nadeem; Zainab Aqeel Khan; Umer Butt; Junaid Ali Shah (Journal of the Pakistan Medical Association)
Radial neck fractures with radial head rotation are very rare and extremely difficult to manage. We present the case of an 11-year-old girl who fell on her outstretched left upper extremity and damaged her left elbow in a road traffic accident. An arthrotomy was performed under a C-Arm fluoroscope, which confirmed the radial head displacement of 180° along with the fracture. The fracture site was reduced and fixed with two Kirschner wires, cutting the wire short at its distal end for a complete closure. Open reduction and internal fixation were followed by casting for five weeks. After two years of follow-up, she had complete pain free range of motion of the affected limb. No post-operative complications have been observed till date. Open reduction and internal fixation with two K-wires is a viable option for such complex injuries. However, further evaluation of outcomes and post-operative complications are required.